Caracterização do perfil antigênico do vírus da doença infecciosa da Bursa de Fabrício por meio da tecnologia de apresentação de antígenos recombinantes em fagos - Capparelli, Fausto Emíllio (2005)
Highly contagious and infectious disease that take hold of young chickens, the Gumboro Disease is caused by a vírus with icosaedral capsid of approximately 60nm and non-enveloped genetic material, belonging to family Birnaviridae and genus Avibirnavirus, because of its genoma composition of double-stranded RNA. This genetic material is bisegmented (A and B). One part of the A segment encodes a polyprotein which is autoclived into VP2, VP3 and VP4 and the other part encodes the protein VP5. The B segment encodes the RdRp VP1. By immunizing SPF chickens, we have obtained sufficient antibody for phage biopanning, followed by a subsequent ELISA immunoassay, in order to verify clone specificity, before sequencing and bioinformatics analysis, using as the genomic and proteomic parameters the European vv/BDV strain UK661. The phage display has allowed us isolating specific peptides, which presented homology with the VP2 protein antigenic regions as well as to other important regions of the remaining viral proteins.